Optimization of Enzymatic Synthesis of Betulinic Acid Amide in Organic Solvent by Response Surface Methodology (RSM) - Nurul Atikah Amin Yusof; Nursyamsyila Mat Hadzir; Siti Efliza Ashari; Nor Suhaila Mohamad Hanapi; Rossuriati Dol Hamid (Universitas Gadjah Mada, 2019)
Optimization of the lipase catalyzed enzymatic synthesis of betulinic acid amide in the presence of immobilized lipase, Novozym 435 from Candida antartica as a biocatalyst was studied. Response surface methodology (RSM) and 5-level-4-factor central-composite rotatable design (CCRD) were employed to evaluate the effects of the synthesis parameters, such as reaction time (20–36 h), reaction temperature (37–45 °C), substrate molar ratio of betulinic acid to butylamine (1:1–1:3), and enzyme amounts (80–120 mg) on the percentage yield of betulinic acid amide by direct amidation reaction. The optimum conditions for synthesis were: reaction time of 28 h 33 min, reaction temperature of 42.92 °C, substrate molar ratio of 1:2.21, and enzyme amount of 97.77 mg. The percentage yield of actual experimental values obtained 65.09% which compared well with the maximum predicted value of 67.23%. The obtained amide was characterized by GC, GCMS and 13C NMR. Betulinic acid amide (BAA) showed a better cytotoxicity compared to betulinic acid as the concentration inhibited 50% of the cell growth (IC50) against MDA-MB-231 cell line (IC50 < 30 µg/mL).